PERANCANGAN MUSEUM MOTOR INDONESIA DENGAN PENDEKATAN EXPERIENCE - Miftha Hurrahman Dahlan; Titian Sarihati (Jurusan Seni Rupa ISBI Bandung, 2019)
Indonesia is one of the countries with the third largest motorcycle users in the world from BPS (Central Statistics Agency) data of motorcycle users in 2017 reaching 113 million motorcycle units. In direct proportion to this, motorcycle enthusiasts in Indonesia can also be seen quite a lot from the increase in visitors each year at motorcycle events on a national and international scale. This phenomenon should be supported by supporting facilities such as transportation museums that can provide knowledge, education, recreation and become a means for motorcycle enthusiasts, custom builders, collectors and the general public who want to find out information about the history of the development of motorcycles in Indonesia. With the existence of the museum can be a place that can facilitate motorcycle enthusiasts and become a means of education about the history of the development of motorcycles in Indonesia.Keywords: Motor Museum, Motorcycles, Informative, Education, Facility________________________________________________________________ Indonesia merupakan salah satu negara dengan pengguna sepeda motor terbesar ketiga di dunia dari data BPS (Badan Pusat Statistik) pengguna sepeda motor di tahun 2017 mencapai 113 juta unit sepeda motor. Berbanding lurus dengan hal tersebut, Penggemar sepeda motor di Indonesia juga cukup banyak dapat dilihat dari meningkatnya pengunjung ditiap tahunnya pada event-event sepeda motor dalam skala nasional dan international. Fenomena tersebut seharusnya dapat didukung dengan fasilitas penunjang seperti museum transportasi yang dapat memberikan pengetahuan, Edukasi, Rekreasi dan menjadi sarana bagi penggemar sepeda motor, Custom builder, Kolektor dan masyarakat umum yang ingin mengetahui informasi tentang sejarah perkembangan sepeda motor di Indonesia. Dengan adanya museum dapat menjadi wadah yang dapat memfasilitasi penggemar sepeda motor dan menjadi sarana edukasi tentang sejarah perkembangan sepeda motor di Indonesia.Kata Kunci: Museum Motor, Sepeda motor, Informatif, Edukasi, Fasilitas